Evaluation of the recent high-degree combined global gravity-field models for geoid modelling over Kenya - Odera, Patroba Achola (Geodesy and Cartography, 2020)
This study carries out an evaluation of the recent high-degree combined global gravity-field models (EGM2008, EIGEN-6C4, GECO and SGG-UGM-1) over Kenya. The evaluation is conducted using observed geoid undulations (18 data points, mainly in Nairobi area) and free-air gravity anomalies (8,690 data points, covering the whole country). All the four models are applied at full spherical harmonic degree expansion. The standard deviations of the differences between observed and GGMs implied geoid undulations at 18 GPS/levelling points over Nairobi area are ±11.62, ±11.48, ±12.51 and ±11.75 cm for EGM2008, EIGEN-6C4, GECO and SGG-UGM-1, respectively. On the other hand, standard deviations of the differences between observed and GGMs implied free-air gravity anomalies at 8,690 data points over Kenya are ±10.11, ±10.03, ±10.19 and ±10.00 mGal for EGM2008, EIGEN-6C4, GECO and SGG-UGM-1, respectively. These results indicate that the recent high-degree global gravity-field models generally perform at the same level over Kenya. However, EIGEN6C4 performs slightly better than EGM2008, GECO and SGG-UGM-1, considering the independent check provided by GPS/levelling data (admittedly over a small area). These results further indicate a good prospect for the development of a precise gravimetric geoid model over Kenya using EIGEN-6C4 by integrating local terrestrial gravity data in a removecompute-restore scheme.